Pembagian peran gender dan dampak kegiatan rehabilitasi: penelitian aspek gender dan tipologi masyarakat dalam kegiatan rehabilitasi hutan di PHBM Sukabumi - Hiyama, C.; Widiarti, A.; Indarti (Badan Penelitian dan Pengembangan Kehutanan (FORDA), 2005)
This study focused on the aspect of gender and diversity, it was found that both men and women were involved in almost all stages of rehabilitation activities. Land clearing is the heaviest work mainly done by men but also supported by women. Women play specific roles in forest rehabilitation activities and about 40% of the total work performed in forest rehabilitation activities. It was concluded that the work distribution between man and women in a household on rehabilitation activities are fairly equal. Men play greater roles in decision making related to rehabilitation activities than women, however, decisions are generally made through discussions between husbands and wives. This means that woman also have power and influence in decision-making process in a family. However, the bargaining power of women within communities is still limited since they have little opportunities to attend formal meetings. In terms of the impacts of forest rehabilitation activities, there is greater differences among various social groups rather than men and women. Landless farmers who don't participate in the program are the marginalized group which can not benefit from the program and tend to have negative impacts of rehabilitation activity. The main obstacles for marginalized group to participate are the limited financial source and access to information. In order to avoid negative impacts on the marginalized groups, a mechanism to enable the marginalized group to participate in forest rehabilitation activities is needed to avoid inequatable land distribution. Information should be distributed equitably to all members of the community before starting the program. Moreover, information meetings should be held not only for men but also for women.